Some aspects of the theory of dynamical systems: a tribute to Jean-Christophe Yoccoz - Crovisier, Sylvain; Krikoria, Raphae; Matheus, Carlos; Senti, Samuel (Paris: Societe Mathematique De France, 2020)
This is the second of two volumes which celebrate the memory of Jean-Christophe Yocc0z. These Volumes present research articles on avrious aspects of the theory of dynamical Systems and related topics that were dear to him
V 2.
Includes bibliographical references
Keywords: Accessibility Aanalytic Circle Diffeomorphisms; Dynamical Systems